Hazard Analysis Critical Control Points (HACCP) Principle 7: Establish Record Keeping and Documentation Procedures - Larry Eubanks; Chad Carr; Ronald H. Schmidt (EDIS)
AN221, a 4-page fact sheet by Larry Eubanks, Chad Carr, and Ronald H. Schmidt, describes how to establish proper recordkeeping as an imperative part of the HACCP system of preventative accountability. Includes references. Published by the UF Department of Animal Science, August 2009.